A review based study on emotional distress and physical pain in oral and head and neck cancer patients pre- and post-chemotherapy - Sanya Mehndiratta; Ravindra Singh; Saanjli Bhandari; Mansha Dadhich (Oral Oncology Reports)
Emotional distress is a psychological response that occurs in the form of mental suffering to an experience that arises from the any negative event or condition. It commonly occurs in patients who suffer from cancer-related physical pain throughout the treatments. Cancer patients face a lot of exhaustion which makes them physically and mentally dysfunctional in their daily lives. However, the Head and Neck Cancer (HNC) patients face some serious issues due to the site of tumour or surgery itself. The current study aims to describe how chemotherapy and physical pain cause emotional distress in HNC patients. Furthermore, the study aims to determine the association between all three factors (Emotional distress, pain, and chemotherapy) and highlight the relevance of care and remediation needs for HNC patients. The literature related to the concerned topic was investigated including empirical research papers, review papers. In total, the authors identified and reviewed 42 articles related to the above-mentioned variables. These articles were obtained from different databases, such as Google Scholar, PubMed, JSTOR and Research Gate. The authors then assessed the full texts of the selected articles for eligibility and extracted data from them. The study revealed that cancer patients who have tolerated physical pain and witnessed the long-term treatment of the process of chemotherapy experience extremely high emotional distress throughout the course. It was also observed that psychological distress is more common in HNC patients than in patients with cancer in other body parts. The main findings of the result indicated that emotional distress was much higher in females. Psychosocial support and palliative care should be integrated to encourage and improve the abilities of cancer-affected patients.